Campaña de comunicación integral para el lanzamiento del complejo habitacional Villa de Atletas - Castañeda Nuñez, Ana Gabriela (2019)
This project aims to develop a communicational proposal for the next brand launch of ‘Villa de Atletas’, a housing complex in Villa el Salvador, for young adults and adults, men and women, from 31 to 59 years of age NSE C and D residing, mainly, in the south of Lima, married or living, with or without children with an interest in settle down with the purchase of a property through some type of financing at the beginning of the year 2020.